Respuesta :

Answer:

2nd term = 11

5th term = 74

Step-by-step explanation:

3n² - 1

n = 2 , 2nd term = 3*2²  - 1

                           = 3*4 -1

                          = 12 - 1

                          = 11

n= 5 , 5th term = 3*5² - 1

                        = 3*25 - 1

                      = 75 - 1

                      = 74

Step-by-step explanation:

in[tex]\tt{3n^2-1 }[/tex] ⠀

If n=2

so,

2nd term=⠀

[tex]\rightsquigarrow[/tex] [tex]\tt{3×2^2-1 }[/tex] ⠀

[tex]\rightsquigarrow[/tex] [tex]\tt{ 3×4-1 }[/tex] ⠀

[tex]\rightsquigarrow[/tex] [tex]\tt{ 12-1 }[/tex] ⠀

[tex]\rightsquigarrow[/tex] [tex]\tt{ 11 }[/tex] ⠀

so,2nd term is 11.

If n=5

so,

5th term =

[tex]\rightsquigarrow[/tex] [tex]\tt{ 3×5^2-1 }[/tex] ⠀

[tex]\rightsquigarrow[/tex] [tex]\tt{ 3×25-1 }[/tex] ⠀

[tex]\rightsquigarrow[/tex] [tex]\tt{75-1 }[/tex] ⠀

[tex]\rightsquigarrow[/tex] [tex]\tt{74 }[/tex]

so 5th term is 74.⠀